(خواتین کے لئے منہج دعوت و ارشاد(سلسلہ مجددیہ کے مکتوبات کی روشنی میں - ڈاکٹر محمد ہمایوں عباس شمس (FIKR-O NAZAR فکر ونظر, 2011)
The sufis proved to be the greatest experts of human psychology among those people who struggled to spread the message of Islam. In performing the obligation for dawah and tazkiah of human spirit they kept an eye on the circumstances and the situation at hand. They also preached and struggled for the well being of females under shariah. This is why there are some female names too in sufis. In subcontinent the great movement of mujaddadi sufis also did not ignore needs for betterment and education of women in society. For the Tazkiah (purification) of beliefs, dealings and knowledge the study of these sufis, letters are of a fundamental importance. The basic directions for betterment and grooming of women can be derived from these letters.